From the grassroots: regional film policy and practice in England - Newsinger, Jack (2010)
This thesis is an analysis of the development of regional film policy and practice in England. From the late 1960s regional film production sectors have gradually emerged from small-scale, under-resourced cottage industries to become significant areas of British film practice. By the mid-2000s the English regions were incorporated into a national film policy strategy based on a network of nine Regional Screen Agencies and centrally coordinated by the UK Film Council. Along with similar developments in Scotland, Wales and Northern Ireland, for many commentators the devolution of film production has questioned the traditional way that British cinema can be understood as a national cinema. This thesis aims to understand how regional film production sectors have developed, what filmmaking practices have characterised them and what these mean for British cinema.